Stability augmentation of wind farm using variable speed permanent magnet synchronous generator - Rosyadi, M.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (The Institute of Electrical Engineers, 2011)
This paper presents a new control strategy of variable speed permanent magnet wind generator for stability augmentation of wind farm including fixed speed wind turbine with Induction Generator (IG). A new control scheme is developed for two levels back-to-back converters of Permanent Magnet Synchronous Generator (PMSG), by which both active and reactive powers delivered to the grid can be controlled easily. To avoid the converter damage, the DC link protection controller is also proposed in order to protect the dc link circuit during fault condition. To evaluate the control capability of the proposed controllers, simulations are performed on two model systems composed of wind farms connected to an infinite bus. From transient and steady state analyses by using PSCAD/EMTDC, it is concluded t at the proposed control scheme is very effective to improve the stability of wind farm for severe network disturbance and randomly fluctuating wind speed.